Conditionally reprogrammed primary airway epithelial cells maintain morphology, lineage and disease specific functional characteristics. Issue 1 (December 2017) - Martinovich, Kelly; Iosifidis, Thomas; Buckley, Alysia; Looi, Kevin; Ling, Kak-Ming; Sutanto, Erika; Kicic-Starcevich, Elizabeth; Garratt, Luke; Shaw, Nicole; Montgomery, Samuel; Lannigan, Francis; Knight, Darryl; et al.
Abstract Current limitations to primary cell expansion led us to test whether airway epithelial cells derived from healthy children and those with asthma and cystic fibrosis (CF), co-cultured with an irradiated fibroblast feeder cell in F-medium containing 10 µM ROCK inhibitor could maintain their lineage during expansion and whether this is influenced by underlying disease status. Here, we show that conditionally reprogrammed airway epithelial cells (CRAECs) can be established from both healthy and diseased phenotypes. CRAECs can be expanded, cryopreserved and maintain phenotypes over at least 5 passages. Population doublings of CRAEC cultures were significantly greater than standard cultures, but maintained their lineage characteristics. CRAECs from all phenotypes were also capable of fully differentiating at air-liquid interface (ALI) and maintained disease specific characteristics including; defective CFTR channel function cultures and the inability to repair wounds. Our findings indicate that CRAECs derived from children maintain lineage, phenotypic and importantly disease-specific functional characteristics over a specified passage range.